Benzoxepinones: A new isoform-selective class of tumor associated carbonic anhydrase inhibitors. Issue 11 (1st June 2020) - Grandane, Aiga; Nocentini, Alessio; Werner, Thomas; Zalubovskis, Raivis; Supuran, Claudiu T.
Graphical abstract: Abstract: Benzoxepinones ("homocoumarins") are identified as a new class of selective inhibitors for tumor associated human carbonic anhydrases (hCA, EC 4.2.1.1) isoforms IX and XII. Similar to coumarins, they do not inhibit or poorly inhibit cytosolic human (h) isoforms hCA I and II, but act as nanomolar inhibitors of the trans-membrane, tumor associated isoforms hCA IX and XII.